2015
DOI: 10.1021/jp510780e
|View full text |Cite
|
Sign up to set email alerts
|

On Surface Order and Disorder of α-Pinene-Derived Secondary Organic Material

Abstract: The surfaces of secondary organic aerosol particles are notoriously difficult to access experimentally, even though they are the key location where exchange between the aerosol particle phase and its gas phase occurs. Here, we overcome this difficulty by applying standard and sub- 1 cm(-1) resolution vibrational sum frequency generation (SFG) spectroscopy to detect C-H oscillators at the surfaces of secondary organic material (SOM) prepared from the ozonolysis of α-pinene at Harvard University and at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
(106 reference statements)
1
36
0
Order By: Relevance
“…Recent studies have confirmed that organic aerosols, which comprise approximately half of the total submicron aerosol mass in the atmosphere, can change from liquid to glassy state at ambient humidity levels and temperatures (Zobrist et al, 2008;Virtanen et al, 2010;Shrestha et al, 2014;Zhang et al, 2015). The effect of temperature may be especially important when aerosol particles are lifted into the free troposphere, where the temperature change can rapidly alter their phase from liquid to glass .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that organic aerosols, which comprise approximately half of the total submicron aerosol mass in the atmosphere, can change from liquid to glassy state at ambient humidity levels and temperatures (Zobrist et al, 2008;Virtanen et al, 2010;Shrestha et al, 2014;Zhang et al, 2015). The effect of temperature may be especially important when aerosol particles are lifted into the free troposphere, where the temperature change can rapidly alter their phase from liquid to glass .…”
Section: Introductionmentioning
confidence: 99%
“…An underestimated viscosity and hence overestimated diffusion coefficient can result in an overprediction of particle mass concentrations as well as an underprediction of gasphase concentrations (Shiraiwa and Seinfeld, 2012). Particle reactivity (Shiraiwa et al, 2011;Kuwata and Martin, 2012a;Zelenyuk et al, 2012;Zhou et al, 2013;Slade and Knopf, 2014), number concentrations (Riipinen et al, 2011), and diameters (Shiraiwa et al, 2013b) can also be influenced by viscosities and diffusion rates, in turn influencing model predictions related to air quality and climate.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive description of the Harvard flow tube reactor used in this work can be found in our previously published work. 25,91 Briefly, β-caryophyllene was introduced into the flow tube as a solution of β-caryophyllene (≥98.5%, Sigma-Aldrich Inc.) diluted in 1-butanol 25,[92][93] at selected injection rates that altered the gas-phase concentration in the range of 300-500 ppb, which subsequently changed the organic particle mass loading in the flow tube.…”
Section: Collection Of Synthetic Secondary Organic Materials (Som) Dermentioning
confidence: 99%
“…Spectra were referenced to the ppp-polarized nonresonant SFG response of gold deposited on fused silica to account for the incident IR energy distribution, and frequencies were calibrated using a polystyrene film. 23,91,[100][101] For the high resolution SFG system, vapor phase compound spectra were acquired by placing 1-2 drops of liquid sample at the edge of a shallow Teflon beaker that was then capped with a fused silica optical window. The vapor was allowed to equilibrate for ~10-45 minutes before spectral data acquisition.…”
Section: Vibrational Sum Frequency Generationmentioning
confidence: 99%